2021
DOI: 10.7759/cureus.15329
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Tumor Margin Shrinkage in the Surgical Resection of Squamous Cell Carcinoma of the Oral Cavity

Abstract: Burns et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A reasonable explanation for this observation could be a difference in tissue shrinkage after resection and in the course of pathological processing. This theory has been discussed by other authors and may be responsible for a part of the observed discrepancies [ 24 27 ]. It seems comprehensible that contractile soft tissue from the tongue or the buccal mucosa displays a different pattern of shrinkage than tissue from the hard palate.…”
Section: Discussionmentioning
confidence: 76%
“…A reasonable explanation for this observation could be a difference in tissue shrinkage after resection and in the course of pathological processing. This theory has been discussed by other authors and may be responsible for a part of the observed discrepancies [ 24 27 ]. It seems comprehensible that contractile soft tissue from the tongue or the buccal mucosa displays a different pattern of shrinkage than tissue from the hard palate.…”
Section: Discussionmentioning
confidence: 76%
“…As perfusion stops, mucosa specimens can shrink significantly (10%-47%) in oral cavity resections. 5,6 Using computer-assisted design software, the scan could be artificially enlarged by tissue-defined percentages. However, this is highly variable depending on tissue type and would need further investigation, especially as advanced tumors (T3/T4) have been reported to shrink less and more irregularly.…”
Section: Discussionmentioning
confidence: 99%
“…A complex topic warranting further investigation is mucosal shrinkage. As perfusion stops, mucosa specimens can shrink significantly (10%‐47%) in oral cavity resections 5,6 . Using computer‐assisted design software, the scan could be artificially enlarged by tissue‐defined percentages.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, variable capacities in margin status prediction could result from the different intraoperative methods used to assess resection margins [ 127 ] and postresection shrinkage [ 131 ]. In particular, the reduction of tumor margin measurements (shrinkage), which occurs between the surgical pre-incision/excision processes and the histopathological evaluation [ 132 ], has been proposed as a potential cause for close pathological margins and requires prudential considerations by surgeons at the initial planning of resection margins.…”
Section: Discussionmentioning
confidence: 99%